Implementasi Bellman-Ford untuk Optimasi Rute Pengambilan Sampah di Kota Palembang - Rezania Agramanisti Azdy; Febriyanti Darnis (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
The problem of waste in big cities in Indonesia is still the main focus of the related department. Generally, the problem is the lack of garbage transport facilities that can beused to transport waste from the temporary shelter (Tempat Penampungan Sementara, TPS) to the final processing site (Tempat Pemrosesan Akhir, TPA). This lack of garbage transport makes the garbage contained in TPS not fully transportable to TPA due to limited capacity and operational time of the relatedservice. In overcoming this problem, optimization of garbage transport facility utilization can be carried out to optimize the capacity of the garbage transported by finding the shortest path that can be traversed by the garbage transporter. This paper aims to apply the Bellman-Ford algorithm for determining waste collection routes. The Bellman-Ford algorithm allows a negative weighting for its edge value, so that it can anticipate the possible costs to be incurred in the selection of the garbage collection path. The stages of this paper were data requirements analysis, design, implementation, and testing. The results of the study are trajectories with a minimum cost from the origin location to the destination location, although it does not pass through all TPS that must be visited.